2018
DOI: 10.3390/en11040735
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experiment Analysis of a Direct-Drive Wave Energy Converter with a Linear Generator

Abstract: Abstract:Coastal waves are an abundant nonpolluting and renewable energy source. A wave energy converter (WEC) must be designed for efficient and steady operation in highly energetic ocean environments. A direct-drive wave energy conversion (D-DWEC) system with a tubular permanent magnet linear generator (TPMLG) on a wind and solar photovoltaic complementary energy generation platform is proposed to improve the conversion efficiency and reduce the complexity and device volume of WECs. The operating principle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The design yields an output voltage of 3.5 V at the rated output power of 3 W [19]. Likewise, a PMLM design by Zhang et al [11] also employed a tubular structure for application at 0.4 m/s speed. The novelty of this design is the asymmetric slot structure which is reported to be able to reduce detent force and enhance the airgap flux density in the design [11].…”
Section: Figure 1 Energy Conversion In Wecmentioning
confidence: 99%
See 2 more Smart Citations
“…The design yields an output voltage of 3.5 V at the rated output power of 3 W [19]. Likewise, a PMLM design by Zhang et al [11] also employed a tubular structure for application at 0.4 m/s speed. The novelty of this design is the asymmetric slot structure which is reported to be able to reduce detent force and enhance the airgap flux density in the design [11].…”
Section: Figure 1 Energy Conversion In Wecmentioning
confidence: 99%
“…Likewise, a PMLM design by Zhang et al [11] also employed a tubular structure for application at 0.4 m/s speed. The novelty of this design is the asymmetric slot structure which is reported to be able to reduce detent force and enhance the airgap flux density in the design [11]. A tubular switched reluctance linear machine (SRLM) has been proposed and analysed by Mendes et al [20] using FEA, mathematical modelling and experiments.…”
Section: Figure 1 Energy Conversion In Wecmentioning
confidence: 99%
See 1 more Smart Citation
“…The point absorber devices with direct drive extraction mechanism are the more efficient systems for ocean wave energy conversion at low velocity oscillations [1]. For this type of conversion devices, linear generators with permanent magnets are generally used [2][3][4][5][6]. However, linear electric machines with permanent magnets need a complicated winding system and are characterized by their elevated construction and assembly costs.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve relatively high quality and efficiency for converting ocean wave energy into electrical energy, various ocean wave energy converters and corresponding electrical machines have been investigated. It was found that linear generators can be used in the direct drive wave energy conversion system, in which it can reduce the complexity of mechanical transmission and improve the reliability and efficiency of the system [6][7][8][9][10][11]. Several electrical generator topologies have been analyzed in the past years [12,13].…”
Section: Introductionmentioning
confidence: 99%